2014
DOI: 10.1111/cei.12374
|View full text |Cite
|
Sign up to set email alerts
|

Increased miR-223 expression in T cells from patients with rheumatoid arthritis leads to decreased insulin-like growth factor-1-mediated interleukin-10 production

Abstract: SummaryWe hypothesized that the aberrant expression of microRNAs (miRNAs) in rheumatoid arthritis (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…For example, decreased expression of miR-145-5p was detected in T cells from patients with myasthenia gravis 46 and systemic lupus erythematosus. 47 MiR-223-3p is overexpressed in T cells from patients with rheumatoid arthritis, 48 indicating the similarity and difference of miRNA expression in different type of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, decreased expression of miR-145-5p was detected in T cells from patients with myasthenia gravis 46 and systemic lupus erythematosus. 47 MiR-223-3p is overexpressed in T cells from patients with rheumatoid arthritis, 48 indicating the similarity and difference of miRNA expression in different type of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis elevated miR-21 and miR-148a expression, which contribute to DNA hypomethylation by targeting the cytosine methyltransferase xDnmt1 and Rasgrp1, which mediate the RAS/MAPK pathway upstream of DNMT1 (77). miR-223 is upregulated in circulating T cells from RA patients (78,79). miR-223 expression is highest in naive RA CD4 + T cells but nearly undetectable in non-naive RA CD4 + T cells and in naive CD4 + T cells from healthy subjects (78).…”
Section: Mirna Regulation Of Peripheral Tolerance and Lymphocyte Funcmentioning
confidence: 99%
“…miR-223 expression is highest in naive RA CD4 + T cells but nearly undetectable in non-naive RA CD4 + T cells and in naive CD4 + T cells from healthy subjects (78). miR-223 targets Igf1r, resulting in decreased IL-10 secretion in response to IGF-1 stimulation (79). Another study found upregulation of miR-143 and miR-223 in CD4 + T cells as well as upregulation of miR-10a and miR-345 in CD19 B cells in patients with SLE (80).…”
Section: Mirna Regulation Of Peripheral Tolerance and Lymphocyte Funcmentioning
confidence: 99%
“…Consistently, Warzecha et al demonstrated that IGF‐1 stimulated production of IL‐10 and inhibited development of caerulein‐induced pancreatitis 20. Lu et al showed that addition of recombinant IGF‐1 stimulated IL‐10 production by activated normal T cells, which was impaired by subsequent transfection with miR‐223 mimic 21. Strle et al reported that prototypical anti‐inflammatory cytokine IL‐10 prevented loss of IGF‐1‐induced myogenin protein expression caused by IL‐1beta 22.…”
Section: Discussionmentioning
confidence: 99%